Implementation of individual placement and support (IPS) into community forensic mental health settings: Lessons learned. (June 2018) - Talbot, Emily; Bird, Yvonne; Russell, Jo; Sahota, Karan; Schneider, Justine; Khalifa, Najat
Introduction: Assessment of the effectiveness of individual placement and support in forensic mental health settings is a relatively new field of research despite evidence demonstrating its effectiveness in generic mental health settings. Method: IPS was implemented into a community forensic mental health setting within a large National Health Service trust in the United Kingdom over 6 months. Using the Consolidated Framework for Implementation Research this paper describes the lessons learned from implementing individual placement and support into such settings. Results: Our findings suggest that implementation of individual placement and support in forensic mental health settings is complex and requires robust planning and collaboration with internal and external agencies. Barriers to implementation included staff attitudes, difficulty engaging employers and lack of employment related performance indicators, and facilitators included the support of service managers and outside groups. Adaptations to the IPS model were made to address challenges encountered, including difficulty starting rapid job searches, concerns about stigma, lack of confidence, uncertainty around employment opportunities, offence restrictions and lack of interest from potential employers. Conclusion: This paper adds to the limited literature in the field. Findings are relevant to practitioners and service providers who wish to implement individual placement and support services for people with mental disorder and offending histories.